The Study on Acute and Subacute Toxicity and Sarcoma-180 Anti-cancer Effects of Triglii Semen Herbal-acupuncture - Chang-Kil Yoo; Ki-Rok Kwon; Byeong-Gil Yu (Korean Pharmacopuncture Institute, 2002)
Objective: The purpose of this study was to investigate the acute and subacute toxicity and sarcoma- 180 anti-cancer effects of Herbal acupuncture with Triglii Semen in mice and rats. Method: Balble mice were injected intraperitoneally with Triglii semen Herbal acupuncture for LD50 and acute toxicity test. Sprague Dawley rats were injected intraperitoneally with Triglii semen Herbal acupuncture for subacute toxicity test. The Triglii semen Herbal acupuncture was injected on Chung-wan(CV12) of mice with S-180 cancer cell line. Results: 1. In acute toxicity test, the LD50 value was 7.49x1000 ml, 0.30ml/kg. 2. The body weights of mice treated with Triglii semen Herbal acupuncture increased during the acute toxicity test. 3. In acute toxicity test of serum biochenrical values of mice, total protein was decreased in treatment groups I, 2 and 3, albunrin was decreased in treatment groups 2 and 3 compared to the control group. GOT was increased in treatment group I and Alk. Phosphatase was increased in treatment groups 1,2 and 3 compared to the normal group(p<0.05). 4.ln subacute toxicity test, severe tissue injury was found in lung and liver. 5. In subacute toxicity test, the body weight was decreased in treatment groups I and 2 compared to the normal group and the weight of liver. lung and kidney were increased in treatment groups 1, 2 and 3 compared to the normal group.(p<0.05) 6. In subacute toxicity test, RBC, HGB and HCT were decreased in treatment groups 1 and 2 compared to the normal group. MCV was increased in treatment group1 compared to the normal group, MCH was increased in treatment groups 1 and 2 compared to the control group in complete blood count test.(p<0.05) 7. In subacute toxicity test, total protein was decreased in treatment groups 1 and 2 compared to the nonnal group, BUN was increased in treatment groups 1 and 2 compared to the nonnal group, creatinine and uric acid were decreased in treatment groups 1 and 2 compared to the normal group, glucose was increased in treatment group 2 compared to the nonnal group, triglycelide was decreased in treatment groups I and 2 compared to the normal group, total cholesterol was increased in treatment groups 1 and 2 compared to the control group. GOT was decreased in treatment group 2 compared to the normal and control group, AIk. Phosphatase was increased in treatment group 1 compared to the normal and control group.(p<0.05) 8. Median survival time was 17days in treatment group 2 for S- 180 cancer cell treated with Triglii semen Herbal acupuncture. 9. Natural killer cell activity was insignificant for S-180 cell treated with Triglii semen Herbal acupuncture.(p<0.05) 10. lnterieukin-2 productivity was decreased for S-180 cell treated with Triglii semen Herbal acupuncture compared to the normal and control group.(p<0.05) Conclusion: According to the results, we can conclude Herbal-acupuncture with Triglii semen caused toxicity, and caused no effects in S-180 cancer cell.